DOSE MAPPING OF GAMMA IRRADIATION CHAMBER (GIC) - Noor, Noramaliza Mohd; Mohd Roslee, Mohd Amirul Azrie; Amirullah, Nur Amalina; Nur Syafinaz Sohini (Asian Journal Of Medical Technology, 2022)
The use of gamma rays to irradiate blood products have been demonstrated to reduce the probability of post-transfusion graft versus host disease. The aim of this study is to investigate the accuracy of a new batch of Gafchromic EBT-XD films to map the homogeneity of gamma radiation dose delivered to the blood bags and identify the lowest and highest levels of radiation exposure to the blood. The Gammacell 3000 Elan Gamma irradiation chamber (GIC) @ Blood Irradiator with Cesium-137 source was used. During the gamma irradiation at an exposure of 8 minutes 51 seconds to deliver a central dose of 25 Gy to the film, the EBT-XD films were placed at the centre of a blood-equivalent phantom. The doses then were measured using dose mapping analysis of Gafchromic EBT-XD film. The responses of EBT-XD films were compared with EBT3 films and GS 300 Dose Mapping Report 2021 prepared by Best Theratronics Dosimetry Laboratory, Canada. Results showed the value of doses obtained from the mapping using EBT-XD were reliable compared with the doses measured in EBT3 film as they were in the range of the acceptable dose ranges for blood irradiation procedures. The mapping with EBT-XD film yielded a minimum dosage of 18 Gy and a maximum exposure of 32 Gy at 8 minutes 51 seconds of irradiation. In conclusion, EBT-XD offered excellent dosimetric characteristics and has a the potential to dose map the blood irradiator.